Climate change, species-area curves and the extinction crisis. - Lewis, O (2006)
An article published in the journal Nature in January 2004-in which an international team of biologists predicted that climate change would, by 2050, doom 15-37% of the earth's species to extinction-attracted unprecedented, worldwide media attention. The predictions conflict with the conventional wisdom that habitat change and modification are the most important causes of current and future extinctions. The new extinction projections come from applying a well-known ecological pattern, the species-area relationship (SAR), to data on the current distributions and climatic requirements of 1103 species. Here, I examine the scientific basis to the claims made in the Nature article. I first highlight the potential and pitfalls of using the SAR to predict extinctions in general. I then consider the additional complications that arise when applying SAR methods specifically to climate change. I assess the extent to which these issues call into question predictions of extinctions from climate change relative to other human impacts, and highlight a danger that conservation resources will be directed away from attempts to slow and mitigate the continuing effects of habitat destruction and degradation, particularly in the tropics. I suggest that the most useful contributions of ecologists over the coming decades will be in partitioning likely extinctions among interacting causes and identifying the practical means to slow the rate of species loss.